TRADITIONAL KNOWLEDGE IN THE PHILIPPINES - Koto, Ismail (Proceeding International Seminar of Islamic Studies, 2024)
This knowledge does not need to be explainable within the philosophical framework of modern science. However, what is important is the community's recognition that this knowledge helps to maintain and improve their health for the sake of social continuity and relationships between them which are based on their own culture, history, heritage and awareness. With this limitation, the meaning of traditional medicine is also very broad because it is very depends, on the recognition of indigenous people as owners. A study cannot be said to be research if it does not have a research method. The research method is a process of collecting and analyzing data that is carried out systematically, to achieve certain goals. Data collection and analysis is carried out naturally, both quantitatively and qualitatively, experimentally and non-experimentally, interactively and non-interactively. The research method used is normative juridical research, namely legal research conducted by examining literature or secondary data. In qualitative research, the process of obtaining data is in accordance with the research objectives or problems, studied in depth and with a holistic approach. Discussions regarding the protection of IPR in developing countries have not succeeded in taking into account cultural differences that influence the understanding of